Cognitive‐behavioral couple therapy for same‐sex female couples: A pilot study. Issue 4 (29th July 2021) - Pentel, Kimberly Z.; Baucom, Donald H.; Weber, Danielle M.; Wojda, Alexandra K.; Carrino, Emily A.
Abstract: Despite comparable levels of relationship satisfaction and intimacy, same‐sex couples break up faster and more often than different‐sex couples, highlighting a need for quality couple therapy. Research suggests that culturally tailored services are desired by same‐sex couples and may be more effective and better received. Although efficacious couple therapies exist to treat relationship distress, they have been overwhelmingly studied with different‐sex couples. Sexual minority (SM) affirming couple therapies have not been systematically developed or evaluated. The current study involved developing and pilot testing a couple therapy tailored for distressed same‐sex female couples. This treatment integrates the SM stress model with the empirically supported cognitive‐behavioral couple therapy framework and is the first culturally tailored couple therapy for same‐sex couples to be empirically evaluated. Therapists delivered the treatment in an open‐trial format to a pilot sample of 11 same‐sex female couples experiencing relationship distress and SM stress. Treatment was delivered with high adherence to the treatment manual. Participants reported high treatment satisfaction. As hypothesized, participants experienced significant decreases in relationship distress and improvements in couple coping with SM stress from pre‐ to post‐therapy. Limitations precluded clear conclusions regarding anticipated improvements in individual mental health. Participants experienced comparable or stronger improvements in relationship functioning compared to couples in a similar benchmark study. Given this is a small pilot study, results are interpreted with caution. Implications for culturally tailoring evidence‐based couple therapy for marginalized groups are discussed. Resumen: A pesar de los niveles comparables de satisfacción con la relación y de intimidad, las parejas del mismo sexo se separan más rápidamente y con más frecuencia que las parejas de distinto sexo, lo cual destaca la necesidad de una terapia de pareja de calidad. Las investigaciones indican que las parejas del mismo sexo desean recibir servicios adaptados a las culturas, los cuales pueden ser más eficaces y mejor recibidos. Aunque existen terapias de pareja eficaces para tratar el distrés en las relaciones, estas se han estudiado en su mayoría con parejas de distinto sexo. Las terapias de pareja dedicadas a las minorías sexuales no se han desarrollado ni evaluado sistemáticamente. El presente estudio implicó el desarrollo y la prueba piloto de una terapia de pareja adaptada para parejas femeninas del mismo sexo con distrés. Este tratamiento integra el modelo de estrés de las minorías sexuales con el marco de la terapia de pareja cognitivo‐conductual respaldado empíricamente, y es la primera terapia de pareja adaptada culturalmente para parejas del mismo sexo que se evalúa empíricamente. Los terapeutas administraron el tratamiento en un formato de estudio abierto a una muestra piloto de 11 parejas femeninas del mismo sexo que sufrían distrés relacional y estrés por minoría sexual. El tratamiento se aplicó con una alta adhesión al manual de tratamiento. Las participantes informaron una alta satisfacción con el tratamiento. Como se planteó en la hipótesis, las participantes disminuyeron considerablemente el distrés relacional y mejoraron en el afrontamiento del estrés por minoría sexual de la pareja después de la terapia respecto de antes de la terapia. Las limitaciones impidieron sacar conclusiones claras con respecto a la previsión de mejorías en la salud mental individual. Las participantes tuvieron mejorías comparables o más marcadas en el funcionamiento de la relación respecto de las parejas de un estudio comparativo similar. Teniendo en cuenta que este es un estudio piloto pequeño, los resultados se interpretan con cautela. Se comentan las implicancias para adaptar culturalmente la terapia de pareja factual para grupos marginados. 摘要: 尽管同性伴侣的关系满意度和亲密程度并不比异性伴侣差，但他们比起异性伴侣而言，分手更快、更频繁，这突出表明需要高质量的伴侣治疗。研究表明，文化针对性的服务是同性伴侣所希望的，而且可能更有效和更受欢迎。尽管存在有效的伴侣治疗方法来治疗关系的不良情况，但它们绝大多数是针对不同性别的夫妻进行研究的。由性少数群体（SM）确认的伴侣治疗方法还没有被系统地开发或评估过。本研究涉及开发和试点测试一种为受困扰的女同性伴侣专门开发的伴侣疗法。该疗法将SM压力模型与经验支持的认知行为情侣疗法框架结合起来，是第一个经过经验评估的针对同性伴侣的文化调适伴侣疗法。治疗师以开放性试验的形式向11对经历关系困扰和SM压力的女同性伴侣提供治疗。治疗是在高度遵守治疗手册的基础上进行的。参与者对治疗的满意度很高。正如假设的那样，从治疗前到治疗后，参与者的关系困扰明显减少，伴侣应对SM压力的情况也有改善。由于条件限制，无法对个人心理健康的预期改善得出明确的结论。与类似的基准研究中的伴侣相比，参与者在关系功能方面有相当或更大的改善。鉴于本研究只是一个小型的试验性研究，对结果的解释要谨慎。本文讨论了为边缘化群体专门开发的循证伴侣治疗的文化意义。